GE_GERICHTE C/19074/2014 vom 28. September 2017 - GE Cour de justice (2017)
SUREXPERTISE ; DROIT DE GARDE ; VISITE ; RELATIONS PERSONNELLES ; LOGEMENT DE LA FAMILLE | CC.273; CC.176; CC.176; CPC.316; CPC.188;